A UFLC‐MS/MS method with a switching ionization mode for simultaneous quantitation of polygalaxanthone III, four ginsenosides and tumulosic acid in rat plasma: application to a comparative pharmacokinetic study in normal and Alzheimer's disease rats. (10th July 2013) - Lv, Chunxiao; Li, Qing; Zhang, Yaowen; Sui, Zhenyu; He, Bosai; Xu, Huarong; Yin, Yidi; Chen, Xiaohui; Bi, Kaishun
Abstract : A fast, sensitive and reliable ultra fast liquid chromatography‐tandem mass spectrometry (UFLC‐MS/MS) method has been developed and validated for simultaneous quantitation of polygalaxanthone III (POL), ginsenoside Rb1 (GRb1), ginsenoside Rd (GRd), ginsenoside Re (GRe), ginsenoside Rg1 (GRg1) and tumulosic acid (TUM) in rat plasma after oral administration of Kai‐Xin‐San, which plays an important role for the treatment of Alzheimer's disease (AD). The plasma samples were extracted by liquid–liquid extraction using ethyl acetate–isopropanol (1:1, v/v ) with salidrdoside as internal standard (IS). Good chromatographic separation was achieved using gradient elution with the mobile phase consisting of methanol and 0.01% acetic acid in water. The tandem mass spectrometric detection was performed in multiple reaction monitoring mode on 4000Q UFLC‐MS/MS system with turbo ion spray source in a negative and positive switching ionization mode. The lower limits of quantification were 0.2–1.5 ng/ml for all the analytes. Both intra‐day and inter‐day precision and accuracy of analytes were well within acceptance criteria (±15%). The mean absolute extraction recoveries of analytes and IS from rat plasma were all more than 60.0%. The validated method has been successfully applied to comparing pharmacokinetic profiles of analytes in normal and AD rat plasma. The results indicated that no significant differences in pharmacokinetic parameters of GRe, GRg1 and TUM were observed between the two groups, while the absorption of POL and GRd in AD group were significantly higher than those in normal group; moreover, the GRb1 absorbed more rapidly in model group. The different characters of pharmacokinetics might be caused by pharmacological effects of the analytes. Copyright © 2013 John Wiley & Sons, Ltd.